Phytotoxic effects of the extracts and compounds isolated from napiergrass (pennisetum purpureum) on Chinese sprangletop (leptochloa chinensis) germination and seedling growth in aerobic rice systems - Tse Seng Chuah; Md Zain Norhafizah; Sahid Ismail (2014)
Chinese sprangletop, a problematic weed in aerobic rice fields, has developed resistance to various groups of herbicides. In search of natural herbicides, the phytotoxic effects of napiergrass extracts on Chinese sprangletop were investigated. Phytotoxicity-directed extraction and fractionation of the culm plus leaves of napiergrass led to the isolation and identification of three major compounds: 2,4-di-tert-butylphenol (2,4-DTBP), cis-9-octadecenoic methyl ester (methyl oleate), and phthalic acid, mono-(2-ethylhexyl) ester (MEHP). These compounds showed different degrees of inhibition against the tested bioassay species. 2,4-DTBP was the most potent of the three compounds and completely inhibited the germination of Chinese sprangletop at the concentration of 0.5 g L−1, followed by MEHP, where 62% inhibition of germination was obtained. In contrast, methyl oleate showed only slight inhibition (< 10%) of germination. A soil bioassay further demonstrated that 2,4-DTBP is a strong inhibitor of root growth and completely prevented root growth of Chinese sprangletop at an application rate as low as 0.60 kg ai ha−1. Under aerobic conditions, 2,4-DTBP at 2.4 kg ai ha−1 reduced the emergence and shoot fresh weight of Chinese sprangletop by more than 60%, with negligible effect on root and shoot growth of aerobic rice seedlings, suggesting that 2.4 kg ai ha−1 2,4-DTBP is the most suitable rate to control Chinese sprangletop without injuring rice seedlings. Reduction in shoot height of rice plant was evident at 0 d after sowing across 2,4-DTBP rates. However, the rice plants became less susceptible with increasing growth stages. The present findings imply that 2,4-DTBP may potentially be developed as a PRE soil-applied natural herbicide for control of Chinese sprangletop and perhaps other weeds in aerobic rice system.